Cephalometrıc Evaluatıon Of Profıle Changes In Class Iı Dıvısıon J Cases By Combıned Heagear Therapy - Semra Ciğer; Mehmet Özgen; Eray Erdoğan (Galenos Yayinevi, 1990)
In the treament of class II division 1 malocclusions, application of extra-oral force traction is an effective means of a treatment modality. The magnitude, duration and direction of the headgear force is as important as the craniofacial growth pattern of the individual patient. Elimination of the overjet and the jaw discrepancy necessiate adjunctive edgewise mechanotherapy. In this regard, retraction of the upper incisors contributes favorably to the soft tissue profile. The implication of the combined headgear traction on the maxilla is evident as it does not cause a rotation of the maxillary complex. Furthermore, it not only inhibits/retards the growth of the maxilla but also frees the mandible to catch up with the maxilla. Consequently, the mandible achieves optimum growth. The smiling line is also positively effected by the growth retardation/inhibition furnished by the combined headgear traction and subsequent incisor retraction and intrusion. These prevent the unsightly exposure of the gums or in other words the "gummy smile". In this paper, cephalometric evaluation of combined headgear treament of class II division I individuals is presented with a control group of similar malocclusion and statistical findings of the study are considered to be significant.